Barriers and facilitators with medication use during the transition from hospital to home: a qualitative study among patients - Sara Daliri; Charlotte L. Bekker; Bianca M. Buurman; Wilma J. M. Scholte op Reimer; Bart J. F. van den Bemt; Fatma Karapinar - Çarkit (BMC, 2019)
Abstract Background During transitions from hospital to home, up to half of all patients experience medication-related problems, such as adverse drug events. To reduce these problems, knowledge of patient experiences with medication use during this transition is needed. This study aims to identify the perspectives of patients on barriers and facilitators with medication use, during the transition from hospital to home. Methods A qualitative study was conducted in 2017 among patients discharged from two hospitals using a semi-structured interview guide. Patients were asked to identify all barriers they experienced with medication use during transitions from hospital to home, and facilitators needed to overcome those barriers. Data were analyzed following thematic content analysis and visualized using an "Ishikawa" diagram. Results In total, three focus groups were conducted with 19 patients (mean age: 70.8 (SD 9.3) years, 63% female). Three barriers were identified; lack of personalized care in the care continuum, insufficient information transfer (e.g. regarding changes in pharmacotherapy), and problems in care organization (e.g. medication substitution). Facilitators to overcome these barriers included a personal medication-counselor in the care continuum to guide patients with medication use and overcome communication barriers, and post-discharge follow-up care (e.g. home visits from healthcare providers). Conclusions During transitions from hospital to home patients experience individual-, healthcare provider- and organization level barriers. Future research should focus on personal-medication counselors in the care continuum and post-discharge follow-up care as it may overcome communication, emotional, information and organization barriers with medication use.